ANALYSIS OF THE DEVICE DESIGN FOR DISCHARGING HEAVY MIXTURES FROM THE SEDIMENTATION CHAMBER - Abdusalomova, Nafisa (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article explores the process of continuously discharging heavy mixtures from the working chamber of a sedimentation device. It examines the designs of the relevant mechanisms and highlights their shortcomings. The necessity of conducting future scientific research aimed at improving the efficiency of devices that discharge heavy mixtures from the sedimentation chamber is substantiated.